Optimization of the Biodiesel Production via Transesterification Reaction of Palm Oil using Response Surface Methodology (RSM): A Review - Nur Aishah Rajali; Salina Mat Radzi; Nur Amalina Mohd Amin; Maryam Mohd Rehan (Institut Kimia Malaysia, 2024)
Volume: 25 Issue: 3 (page :42-53)